Strain Rockbursts Simulated by Low-Strength Brittle Equivalent Materials - Lang Li; Mingyang Wang; Pengxian Fan; Haiming Jiang; Yihao Cheng; Derong Wang (Advances in Materials Science and Engineering)
This paper presents experimental study on rockbursts that occur in deep underground excavations. To begin with, the boundary conditions for excavation in deep underground engineering were analysed and elastic adaptive boundary is an effective way to minimize the boundary effect of geomechanical model test. Then, in order to simulate an elastic adaptive loading boundary, Belleville springs were used to establish this loading boundary. With the aforementioned experimental set-ups and fabrication of similarity models for test, the phenomena of strain mode rockbursts were satisfactorily reproduced in laboratory. The internal stress, strain, and convergences of the openings of the model were instrumented by subtly preembedded sensors and transducers. Test results showed that, with an initial state of high stress from both upper layers’ gravitational effects and in situ stress due to tectonic movements, the excavation brings a dramatic rise in the hoop stress and sharp drop in radial stress, which leads to the splitting failure of rock mass. Finally a rockburst occurred associated with the release of strain energy stored in highly stressed rock mass. In addition, the failure of the surrounding rock demonstrated an obvious hysteresis effect which supplies valuable guide and reference for tunnel support. Not only do these results provide a basis for further comprehensive experiments, but also the data can offer assisting aids for further theoretical study of rockbursts.